Concomitant pheochromocytoma and hyperaldosteronism in a 47-year-old man: a case report - Fatemeh Majidi; Ali Shabbak; Shadi Nazarizadeh; Aryan Madady (Journal of Medical Case Reports)
Abstract Background The coexistence of pheochromocytoma and hyperaldosteronism is a rare and clinically significant finding with diagnostic challenges that need to be considered in the workup of patients with hypertension. Case presentation This case report describes a 47-year-old Iranian man who initially presented with cold symptoms, chills, and headaches. Despite being diagnosed with panic disorder, his symptoms worsened, leading to a systolic blood pressure crisis. The results indicated elevated levels of 24-hour urine vanillylmandelic acid, metanephrine, and normetanephrine, suggesting increased catecholamine levels. An increase in serum aldosterone was also observed. Further evaluation revealed a 4 cm left adrenal mass and subsequent tests confirmed the diagnosis of pheochromocytoma and hyperaldosteronism. The patient underwent left adrenal gland resection, resulting in complete resolution of symptoms and normalization of test results. Conclusion This case highlights the importance of considering rare coexisting endocrine disorders in patients presenting with hypertension. Appropriate diagnosis and management of concomitant pheochromocytoma and hyperaldosteronism are crucial for favorable outcomes and may offer insights into potential overlaps in disease pathways.